Properties of [(111)In]-labeled HIV-1 tat peptide radioimmunoconjugates in tumor-bearing mice following intravenous or intratumoral injection. - Cornelissen, B; McLarty, K; Kersemans, V; Scollard, D; Reilly, R (2008)
INTRODUCTION: Our objective was to evaluate the tumor and normal tissue distribution and nuclear importation properties of [(111)In]-mouse IgG (mIgG) conjugated to tat peptides (GRKKRRQRRRPPQGYG) in athymic mice with subcutaneous BT-474 human breast cancer xenografts. METHODS: Tumor and normal tissue uptake was compared after intravenous (iv) or intratumoral injection of [(111)In]-mIgG-tat and [(111)In]-mIgG. Area under the curve (AUC) was estimated for blood, liver, spleen, kidneys and tumor. Nuclear localization was measured by subcellular fractionation and estimated by microdosimetry. Imaging studies were performed with a gamma-camera. RESULTS: [(111)In]-mIgG-tat was eliminated from the blood and normal tissues two- to threefold more rapidly after iv injection than [(111)In]-mIgG. Tumor uptake was 4-5% injected dose per gram (%ID/g). Tumor radioactivity after intratumoral injection was initially very high (146-154 %ID/g), but declined 12- to 14-fold by 144 h postinjection. There was greater retention of [(111)In]-mIgG-tat in BT-474 tumors after intratumoral than iv injection, and the AUC (610+/-157 %ID h) was threefold greater than for intratumorally injected [(111)In]-mIgG (200+/-37 %ID h). Tat peptides increased nuclear localization of [(111)In]-mIgG after iv injection in tumor, kidney and liver cells, but only in tumor cells after intratumoral injection. Tumors were not imaged after iv administration but were predominant with intratumorally injected [(111)In]-mIgG and [(111)In]-mIgG-tat. Estimated radiation doses to the nucleus of tumor cells from intratumoral [(111)In]-mIgG-tat were 2.8x10(3) mGy/MBq and were 15-fold higher than for iv injection. CONCLUSION: [(111)In]-labeled tat immunoconjugates may have potential for imaging intracellular epitopes or localized Auger electron radiotherapy of tumors.